A LED-based measurement system for affinity between bitumen and aggregate. (15th April 2015) - Yuan, Jun; Dong, Wen-Jiao; Chen, Jia-Jun; Zhang, Shen; Qian, Wu-Bin; Sun, Wei-Wei
Highlights: An automatic measurement system is built to estimate the affinity between bitumen and aggregate. LED lighting is used to highlight the difference among bitumen, aggregate and background. The digital image processing techniques eliminate the uncertainty of manual observation. Abstract: When determining the affinity between bitumen and aggregate the result is affected by subjective factors due to the visual estimation. The images of the test sample taken under natural light still have the disadvantage of inaccurate discrimination between bitumen, aggregate and the background. Therefore, in this paper, a Light-Emitting Diode (LED)-based measurement system is presented. In this system, LED modules are symmetrically embedded in the inner surface of a black box as the directional light source. Test specimens are placed on a white platform, which is at the bottom of the black box. Then a digital camera captures images through a hole in the top of the black box. These measures minimize the interference of natural light, increase the contrast ratio of the bitumen, aggregate and background, and make the clear boundary. Then the affinity between the bitumen and aggregate is calculated by digital image-processing software. The LED-based measurement and process system greatly improves the accuracy of the affinity test results by eliminating the uncertainty of human observation.